"Me-search": Challenges and opportunities regarding subjectivity in knowledge construction. (13th November 2017) - Gardner, Susan K.; Hart, Jeni; Ng, Jennifer; Ropers-Huilman, Rebecca; Ward, Kelly; Wolf-Wendel, Lisa
Abstract : Purpose: The purpose of this paper is to discuss the experiences with me-search among scholars in the field of education, defined as the conduct of research about one's own identity or in one's own setting. Design/methodology/approach: Centered around the tensions inherent in the training received around objectivity and subjectivity, these individuals discuss how they came to conduct me-search and the challenges inherent in it, with a particular focus on the teaching and advising of students conducting this kind of qualitative work. Findings: ApplyingRichardson and St. Pierre's (2005) concepts of writing stories, the following reflections provide a grounding of the "me" in methodology, with an eye toward using this methodology to create social change. Originality/value: While this is a common research approach, relatively little guidance exists on the practice of "me-search", particularly for young scholars.